Vancomycin- and Poly(simvastatin)-Loaded Scaffolds with Time-Dependent Development of Porosity - Thilanga Liyanage, A. D. (ACS Appl Bio Mater, 2019)
Biodegradable scaffolds are widely use in drug delivery and tissue engineering applications. The scaffolds can be modified to provide the necessary mechanical support for tissue formation and to deliver one or more drugs to stimulate tissue formation or for the treatment of a specific condition. In the current study, we developed biodegradable scaffolds that have the potential for dual drug delivery. The scaffolds consisted of simvastatin-containing prodrug, poly(simvastatin) entrapped in poly(β-amino ester) (PBAE) porogen particles and vancomycin encapsulated in poly(lactic-co-glycolic acid) (PLGA) microspheres, which were fused together around the PBAE porogens to create a slow-degrading matrix. Upon hydrolysis, poly(simvastatin) releases simvastatin acid, which has angiogenic and osteogenic properties, while the PLGA microspheres release vancomycin as an antibacterial agent. Degradation of PBAE porogens through hydrolysis of ester linkages led to the development of porosity in a controlled manner and led to water penetration that facilitated hydrolysis of PLGA. Higher porogen loading (~60% by weight) gave rise to ~70% interconnected porosity with pore spacing of ~180 μm. This open volume facilitated simvastatin acid release upon hydrolysis and entrapped vancomycin release via diffusion through and degradation of PLGA. During the study, ~162 μg of simvastatin acid and ~18 mg vancomycin were released from the highest porosity scaffolds. Bioactivity studies showed that released simvastatin acid stimulated preosteoblastic activity, indicating that scaffold fabrication did not damage the polymeric prodrug. Regarding mechanical properties, compressive modulus, failure strain, and failure stress decreased with increasing PBAE porogen content. These dual drug releasing scaffolds with controlled development of microarchitecture can be useful in bone tissue engineering applications.